PENODAAN AGAMA WABAH TERHADAP PLURALITAS AGAMA DI INDONESIA PENERAPAN DELIK KUHP DALAM KASUS PENODAAN AGAMA - Muhammad Darwis (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
The Indonesian nation is a pluralistic nation, especially in religiosity. This is becoming a nation is rich in differences. The fact that it can not deny, that, the existence of normative standards that are owned by their respective religion. These religious norms when viewed at a glance, only to the extent of universal teachings and values of religious open to consensus. However, if further review, in these religions there are also religious norms that are partial-specific, such as religious doctrine, which is certainly difficult strived occurrence of a harmony. This is based on the reality that everything must be followed by a doctrinal interpretation, and in turn will establish religious fanaticism among his people. Of this fact, it can be ascertained that the conflict across religious doctrine among the adherents of a religion will continue. Hence, it is necessary to build an awareness of the plurality of religions in this country. Pancasila as the nation's basic philosophy is the ideal model of a plurality basis, Pancasila is a result of the contemplation of the founding fathers of the open-minded and tolerant in religion and was the embodiment of traditional values and cultural heritage. Order to create a harmonious and democratic life in this country, it is important to review the Pancasila as the foundation of religious plurality in Indonesia. Pancasila is the objectification of the universal values in every religion and belief, Pancasila is the philosophical basis of the intersection or along the Indonesian people in religion, with the supreme deity, please indicate that this nation with living up to her religion, Indonesia has one the same religiosity, namely joint recognition of the supreme deity. Pancasila is a social contract and state and nation.